A Modified TODIM Based on Compromise Distance for MAGDM with q-Rung Orthopair Trapezoidal Fuzzy Numbers. (9th November 2021) - Wan, Benting; Huang, Juelin; Zhang, Xiaolu
Abstract : The q -rung orthopair fuzzy number ( q -ROFN) has been recently developed by Yager and has been widely applied in handling real-life decision-making problems. To enhance its usefulness in dealing with complex practical issues, this paper first proposes the new concept of q -rung orthopair trapezoidal fuzzy numbers ( q -ROTrFNs) which is a new and useful extension of q -ROFNs. Then, we investigate the operation of q -ROTrFNs and develop a new ranking method for q -ROTrFNs. We also propose a new q -rung orthopair trapezoidal fuzzy Hamming distance measure. More important, we develop a useful q -rung orthopair trapezoidal fuzzy modified TODIM group decision-making method. In this method, a new q -rung orthopair trapezoidal fuzzy weighted aggregating ( q -ROTrFWA) operator is developed to integrate individual decision matrices into the collective decision matrix, and a q -rung orthopair trapezoidal fuzzy distance measure-based compromise approach is proposed to determine the relative dominance degree of alternatives. It is worth to mention that the modified TODIM method not only expands the freedom of decision makers but also allows decision makers to choose the appropriate risk preference parameter. Finally, a case study on health management of hypertensive patients is conducted to demonstrate the feasibility of the modified TODIM group decision-making method, and the developed method is further verified by comparison analysis with the existing methods and sensitive analysis of different parameters.